HUBUNGAN DURASI KERJA, BEBAN KERJA FISIK, DAN KELELAHAN KERJA TERHADAP TERJADINYA KEJADIAN MINOR INJURY PADA PABRIK TAHU X KOTA SEMARANG - Annisa Fitriani; Ekawati Ekawati; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2021)
Minor Injury is a work accident that is experienced by someone while working and did not cause a loss of productive work time of more than 2x24 hours that can be cured with first aid kit. However, minor injuries cannot be ignored, if there is no identification of the problem it can lead to major injury or even fatality. According to the Loss Causation Theory Model, work accidents are caused by direct causes (Unsafe Action and Unsafe Conditions) and basic causes (human factors and occupational factors). Most of the Tofu X Factory workers had experienced minor injuries. This study aimed to analyze the correlation between work duration, physical workload and work fatigue with the occurrence of minor injuries. The type of this research was quantitative with cross-sectional studies. The sample of this study was the entire population of 35 workers. The instruments of this study were questionnaire sheets for work duration variables and IFRC standard questionnaires for work fatigue variables, measurement of physical workload variables using SNI 7269: 2009 standards. Data analysis used was Chi Square test. The results showed that there were 60% workers experienced minor injury events, 57,1% workers had over work duration, 65,7% workers had heavy physical workloads, and 80% workers experienced moderate fatigue. The results of the chi-square analysis showed that there was no correlation between work duration (p = 0.163) with the occurrence of minor injuries. There was a correlation between physical workload (p = 0.026), and work fatigue (p = 0.028) with the occurrence of minor injuries. Researchers advised the Tofu X Factory to provide drinking water spot and first-aid kit close to the work area.